Understanding diagnostic settings and carer experiences for dementia diagnosis in Australia - Ng, Natalie Su Quin; Ayton, Darshini; Workman, Barbara; Ward, Stephanie Alison (Internal medicine journal, 2021)
Background Australian guidelines advocate referral to comprehensive memory services for dementia diagnosis, but many patients may be diagnosed elsewhere. Aims To determine common settings for dementia diagnosis in Australia and to compare patient and carer experience between settings. Methods Exploratory cross‐sectional study of patients with dementia admitted to a Melbourne sub‐acute hospital. Patients who had capacity to participate were included; carers were recruited for patients without capacity. Participants completed an interviewer‐administered survey which asked them to recall the diagnostic setting, discussions about diagnosis and management (clinical care) and overall experience of diagnosis. Descriptive statistics were applied and open‐ended questions were analysed using inductive and deductive coding approaches. Results From 81 eligible participants, 74 consented to participate (one patient, 74 carers). Participants reported dementia diagnosis occurred a median of 24 months before interview, in the following settings: hospitals (31.3%), private specialist clinics (29.7%), memory clinics (14.9%), general practice (13.5%), community health services (9.5%) and residential care (1.4%). Recall of discussions about dementia‐modulating medications was higher in participants diagnosed in memory clinics and private specialist clinics (70%) compared to other settings (15%) (P < 0.001). Discussion about living circumstances was highest in hospitals (87% vs 40%) (P < 0.001). One third of participants reported dissatisfaction with their experience. Reported satisfaction was highest for memory clinics. Conclusion Results suggest majority of people with dementia are diagnosed outside memory services. Significant variability exists in experiences between services, with a high proportion of participants expressing dissatisfaction with their experience with dementia diagnosis. Strategies to standardise diagnosis of dementia, measure and improve quality of care across all settings are required.